P218 Accuracy of Ultrasonography in Assessing Disease Activity in Pediatric Ulcerative Colitis: Preliminary Results of a two-center study. (21st January 2022) - Marra, A; Terracciano, F; Bossa, F; Pastore, M R; Marseglia, A; Di Rodi, A; Valvano, M R; Carparelli, S; Ippolito, M A; D'Altilia, M; Ferrara, D; Esposito, F; et al.
Abstract: Background: Ulcerative colitis (UC) is an inflammatory bowel disease involving rectum and colon. Transabdominal bowel ultrasound (TBUS) is a non-invasive technique evaluating inflamed colonic segments. Previous studies showed optimal concordance between TBUS and endoscopy in the colon, but suboptimal in the rectum. Transperineal ultrasound (TPUS) of the rectum achieved high agreement with endoscopy in adult UC patients. Aim of this study was to assess the accuracy of ultrasound in evaluating disease activity in pediatric UC patients by means of TBUS and TPUS Methods: Pediatric UC patients were enrolled in two IBD centers from March to November 2021. Disease activity was determined using PUCAI score and Mayo Endoscopic Subscore (MES). TBUS and TPUS were performed within a week from endoscopy. MES ≤ 1, bowel wall thickness ≤ 3mm in the colon and ≤ 4mm in the rectum were defined as remission. A concordance analysis comparing endoscopy and US was performed. Results: Eighteen patients were enrolled with a mean age of 9.1 ± 4.0 years and a mean disease duration of 2 ± 2.9 years.10 patiens had pancolitis, 2 distal colitis, 4 proctitis. Fifteen patients had endoscopic active disease (2 mild, 12 moderate and 1 severe), and 3 were in remission. Good correlation at the Cohen κ-value between endoscopy and TPUS was observed (K= 0.68). In the evaluation of colon with TBUS the same concordance was found in right (K= 0.64), the transverse (K= 0.75) and in the left colon (K= 0.77), while moderate in the sigma (K= 0.55). Conclusion: If these results will be confirmed in a larger study, the combination of TBUS and TPUS could represent a non-invasive technique to assess disease activity in UC children.